3-component (N, Fe, Co) atomically dispersed ORR catalysts prepared by laser-driven decomposition of organic precursors - Ekaterina Pakrieva; Javier Hernandez-Ferrer; Gema Martinez; Francisco Balas; Enrique García-Bordeje; Alejandro Anson-Casaos; Laura Simonelli; Fernando Bartolome; Ana M. Benito; Wolfgang K. Maser; Jose L. Hueso; Jesus Santamaria (Chemical Engineering Journal, 2025)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Laser driven generation of single atom Fe-N-C catalysts for the oxygen reduction reaction - Ainhoa Madrid; Álvaro Tolosana-Moranchel; Álvaro García; Sergio Rojas; Fernando Bartolome; Ekaterina Pakrieva; Laura Simonelli; Gema Martinez; Jose L. Hueso; Jesus Santamaria (Chemical Engineering Journal, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Metabarcoding and metabolome analyses of copepod grazing reveal feeding preference and linkage to metabolite classes in dynamic microbial plankton communities - Jessica L. Ray; Julia Althammer; Katrine S. Skaar; Paolo Simonelli; Aud Larsen; Diane Stoecker; Andrey Sazhin; Umer Z. Ijaz; Christopher Quince; Jens C. Nejstgaard; Marc Frischer; Georg Pohnert; et al. (Molecular Ecology, 2016)
In order to characterize copepod feeding in relation to microbial plankton community dynamics, we combined metabarcoding and metabolome analyses during a 22‐day seawater mesocosm experiment. Nutrient amendment of mesocosms promoted the development of haptophyte ( Phaeocystis pouchetii )‐ and diatom ( Skeletonema marinoi )‐dominated plankton communities in mesocosms, in which Calanus sp. copepods were incubated for 24 h in flow‐through chambers to allow access to prey particles ( P. pouchetii , were passively consumed or even negatively selected according to our indicator. Our analysis of the relationship between Calanus grazing ratios and intracellular metabolite profiles indicates the importance of carbohydrates and lipids in plankton succession and copepod–prey interactions. This molecular characterization of Calanus sp. grazing therefore provides new evidence for selective feeding in mixed plankton assemblages and corroborates previous findings that copepod grazing may be coupled to the developmental and metabolic stage of the entire prey community rather than to individual prey abundances.

Iron speciation in minerals and glasses probed by $$\hbox{M}_{2/3}$$ M 2 / 3 -edge X-ray Raman scattering spectroscopy - A. Nyrow; C. Sternemann; M. Wilke; R. A. Gordon; K. Mende; H. Yavaş; L. Simonelli; N. Hiraoka; Ch. J. Sahle; S. Huotari; G. B. Andreozzi; A. B. Woodland; et al. (Contributions to Mineralogy and Petrology, 2014)

Site response studies and seismic microzoning in the Middle Aterno valley (L’aquila, Central Italy) - G. Lanzo; F. Silvestri; A. Costanzo; A. d’Onofrio; L. Martelli; A. Pagliaroli; S. Sica; A. Simonelli (Bulletin of Earthquake Engineering, 2011)

Radiolabelling of engineered nanoparticles for in vitro and in vivo tracing applications using cyclotron accelerators - N. Gibson; U. Holzwarth; K. Abbas; F. Simonelli; J. Kozempel; I. Cydzik; G. Cotogno; A. Bulgheroni; D. Gilliland; J. Ponti; F. Franchini; P. Marmorato; et al. (Archives of Toxicology, 2011)

Recorded ground motion and site effects evaluation for the April 6, 2009 L’Aquila earthquake - M. Maugeri; A. L. Simonelli; A. Ferraro; S. Grasso; A. Penna (Bulletin of Earthquake Engineering, 2011)

Quantitative PCR to estimate copepod feeding - Jens C. Nejstgaard; Marc E. Frischer; Paolo Simonelli; Christofer Troedsson; Markus Brakel; Filiz Adiyaman; Andrey F. Sazhin; L. Felipe Artigas (Marine Biology, 2008)